Electron Microscopic Study of the Effects of Preeclampsia on the Placental Endothelial Cells Ultra Structures during Pregnancy - alkasiy, Kawkab Saleem; Al-Habib, . May Fadil; Abdulshaheed, Nahidh Addai (AL-Kindy College Medical Journal, 2010)
Background: Preeclampsia occurs in 3-5% ofpregnancies and is a major cause (12-20 %) ofmaternal mortality in developed countries. It is theleading cause of preterm birth and intra-uterinegrowth restrictions (IUGR).Objective: The study was designed to determine anddemonstrate the ultra structural changes ofendothelial cells in placenta of women suffering fromhypertensive disease.Patients & Methods: Placental samples wereobtained from two groups of pregnant womengroups (preeclamptic and normal pregnant women).The specimens were fixed in 2.5% gluteraldehydeand preceded for electron microscopic examination.Results: Placenta of women with preeclampsia hasshown marked degenerative changes in bothendothelial and trophoblastic cells. These changeswere represented by precipitation of fibrin with theaccumulation of platelets in capillary lumen.Abundance of collagen fibers precipitate in the apicalregion of both endothelial cells and trophoblasts, withthickening of endothelial basement membrane.Conclusion: All histological changes or lesionsobstruct the continuous conduction from maternalsurface of the trophoblasts through fetal capillaryendothelium causing endothelial dysfunction